A new multi-criteria model based on interval type-2 fuzzy sets and EDAS method for supplier evaluation and order allocation with environmental considerations. (October 2017) - Keshavarz Ghorabaee, Mehdi; Amiri, Maghsoud; Zavadskas, Edmundas Kazimieras; Turskis, Zenonas; Antucheviciene, Jurgita
Highlights: A new approach is proposed for supplier evaluation and order allocation. Environmental and economic criteria are considered in the proposed approach. Interval type-2 fuzzy sets and the EDAS method are used for supplier evaluation. A multi-objective linear programming is proposed for order allocation. A sensitivity analysis is made to examine effects of environmental criteria on the model. Abstract: Nowadays environmental performance of suppliers becomes more important because of competitive conditions. Besides, the economic performance has been a significant factor for companies to choose their suppliers. In this paper, a new integrated model is proposed for supplier evaluation and order allocation which considers both environmental and economic factors. We use the EDAS (Evaluation based on Distance from Average Solution) method and interval type-2 fuzzy sets for evaluation of suppliers with respect to environmental criteria. According to this evaluation two parameters are defined for each supplier: positive score and negative score. These parameters, together with cost parameters, are utilized to propose a multi-objective mathematical model for determination of order quantity from each supplier. A numerical example is used in this paper to show the applicability of the proposed integrated model. Also, a sensitivity analysis is made to examine the effect of weighting environmental criteria on total purchasing cost and quantity of order from each supplier. The results show that the proposed model is efficient and applicable for real-world problems.